Dengue: experience from a tertiary care centre in Northern Karnataka, India - Waheed, Mohammad A. (International Journal of Research in Medical Sciences, 2019)
Background: Epidemiology of dengue infection is evolving, and research gap exists in the region. The clinical features, laboratory parameters, complications and treatment outcomes of patients diagnosed of dengue infection at a tertiary care centre were analysed in the present study. Methods: More than 12 years old patients, presenting with features suggestive of acute febrile illness were subjected to detailed history taking and thorough clinical examination. All the suspected cases were further evaluated with complete blood count, liver function test, kidney function test, along with ultrasonography of abdomen. Blood samples were tested for dengue antibodies (IgG and IgM) by hemagglutination inhibition method for confirmation of the diagnosis. The clinical course was closely monitored during hospital stay and complications and deaths, if any, were noted. Results: Total 140 patients were studied. Fever (100%), headache (80%) and myalgia (73.6%) were the commonest symptoms. Thrombocytopenia (136, 97.1%) was the commonest hematological finding, while severe thrombocytopenia (<50,000/cu. mm) was observed in 38 (27.1%) cases. Hepatomegaly (61, 43.6%), splenomegaly (42, 30.0%), ascites (54, 38.6%), pleural effusion and gall bladder edema (18, 12.9% each) were the commonest findings on ultrasonography. Shock and ARDS were the major complications. Conclusions: Dengue remains an important public health problem even at a tertiary care centre and strong suspicion is needed in adult patients with acute febrile illness. The management should focus on averting shock and ARDS, which would help in larger aim of reduction in mortality.